Boom and gloom - Povel,P; Sertsios,G; Kosova,R; Kumar,P (Journal of Finance, 2016)
We study the performance of investments made at different points of an investment cycle. We use a large data set covering hotels in the U.S., with rich details on their location, characteristics and performance. We find that hotels built during hotel construction booms underperform their peers. For hotels built during local hotel construction booms, this underperformance persists for several decades. We examine possible explanations for this long-lasting underperformance. The evidence is consistent with information-based herding explanations.